Gold medal nutrition - Cardwell, Glenn 1956- (Human Kinetics, 2012)
Expanded and updated, the popular Gold Medal Nutrition is back and more relevant to athletes than ever. The fifth edition sports a new look, illustrations, and current discussions of key topics, like what nutrients are needed for peak performance, how best to plan food purchasing and how to control body fat stores and gain muscle. Clear and concise, it is a practical resource for recreational and elite athletes, coaches and health professionals. With the easy-to-follow format in Gold Medal Nutrition, readers can find the advice they need in a matter of seconds. Glenn Cardwell created a resource that contains universal principles that anyone will find useful. In a comprehensive--yet accessible--text, Cardwell explains how to get enough protein, find the best nutritional supplements, eat to bulk up, select the best pre-sport meals, drink the best fluids for sports, and travel well and avoid jet lag. The explanations of the physiology behind fuel intake and muscle contraction will be useful to athletes who want to gain a competitive edge in any sport. The book explains how to build endurance and energy with the right mix of protein, carbohydrate, vitamins and liquids. Particularly helpful are the tips for burning fat, building muscle and losing weight safely and sensibly. Readers will feel more confident eating out, reading food labels and even choosing supplements as they integrate these guidelines into their daily lives.